2019
DOI: 10.1101/531905
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental Changes in Movement Related Brain Activity in Early Childhood

Abstract: In a previous MEG study of movement-related brain activity in preschool age children, we reported that pre-movement fields and sensorimotor cortex oscillations differed from those typically observed in adults, suggesting that maturation of cortical motor networks is still incomplete by late preschool age (Cheyne et al., 2014). Here we describe the same measurements in an older group of school-aged children (6 to 8 years old) and an adult control group, in addition to repeated recordings in seven children from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Studies of sensorimotor activity in developing populations typically focus on the alpha or mu frequency bands, and little is known about the development of beta band activity in infancy (Cuevas et al, 2014; Perone & Gartstein, 2019). It has recently been shown that, similar to alpha, there are age-related changes in beta frequency and power (He et al, 2019; Johnson et al, 2019; Rayson et al, 2022; Trevarrow et al, 2019) from infancy to adulthood. In infancy, the peak beta frequency is 15 Hz (Rayson et al, 2022), but movement-related artifacts from facial and arm movements also occur around this frequency (Georgieva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of sensorimotor activity in developing populations typically focus on the alpha or mu frequency bands, and little is known about the development of beta band activity in infancy (Cuevas et al, 2014; Perone & Gartstein, 2019). It has recently been shown that, similar to alpha, there are age-related changes in beta frequency and power (He et al, 2019; Johnson et al, 2019; Rayson et al, 2022; Trevarrow et al, 2019) from infancy to adulthood. In infancy, the peak beta frequency is 15 Hz (Rayson et al, 2022), but movement-related artifacts from facial and arm movements also occur around this frequency (Georgieva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The role of development processes in this case is also supported by the fact that players of this age in their sports training do not yet apply mental practice, which is often based on visualization [ 3 , 4 ]. Moreover, a study involving neurophysiological methods, such as magnetoencephalography, showed some linear changes in the organization of movement-related brain activity in school-aged children at a different age [ 53 ]. The study showed that the magnitude of mu (8–12 Hz) and beta (15–30 Hz) bands are linear increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…For the motor cortex hand region localiser analysis, trials were prefiltered with a bandpass of 0-100 Hz and epoched with respect to the button press onset into 1.5 s segments (−500 to +1,000 ms), encompassing the established time course of beta-band desynchronisation (several hundred ms prior to and after the button press) and "rebound" synchronisation (several hundred ms starting about 500 ms after the button press) (see Cheyne, 2013;Cheyne et al, 2014;Johnson et al, 2020). Following the maximal contrast approach used for the speech analysis, the SAM pseudo-T analysis used a sliding active window of 200 ms duration starting from 600-800 ms, (step size 10 ms, 10 steps), a fixed baseline window from 0 to 200 ms, and bandpass of 18-22 Hz.…”
Section: Meg Source Reconstruction Of Speech Motor Cortex Methodsmentioning
confidence: 99%